Video Analysis "Bisa Kembali Normal? Obat Covid-19 Sudah Ditemukan!!" From Communication Philosophy Perspective - Islam, Karem Rouby (Syntax Literate, 2021)
The video entitled “Bisa Kembali Normal? Obat Covid-19 Sudah Ditemukan!!” is a video containing an interview between Anji and Hadi Pranoto who claims that he has succeeded in finding a Covid-19 antibody drug, that can prevent and cure patients who have been infected with the coronavirus in just 2-3 days. Many experts also doubt Hadi Pranoto's statements in the video. With the many reactions from the public regarding the video, Cyber Indonesia General President reported Anji and Hadi in August 2020 of violating laws in Indonesia. This article uses a Descriptive Analytic Method. This Article aims to explain the concepts of Human Understanding and Communicating Effectivity in Communication Philosophy. The Concept of Human Understanding is the information provided will form an understanding in society, and the Concept of Communication Effectivity is information/ideas that are conveyed that will effectively change people's behavior. In this case, it was understood that Hady Pranoto had found an anti-COVID-19 drug that could prevent and cure. Then from the information provided, it will result in those who agree to believe what Hadi Pranoto said, will buy the antibody-drug, but those who disagree such as the experts will deny the information provided by Hadi Pranoto, which can also be considered as hoax news. This effect will affect the behavior of people watching the video, which leads to community disorders.